Repeated focal mollusciciding for snail control in a sugar-cane area of northeast Brazil - Pieri, Otávio S. (1995)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Biologia. Laboratório de Ecologia e Controle de Moluscos Vetores. Rio de Janeiro, RJ, Brasil.